2012
DOI: 10.7196/samj.5768
|View full text |Cite
|
Sign up to set email alerts
|

Plasma sarcosine does not distinguish early and advanced stages of prostate cancer

Abstract: The identification of prostate cancer remains problematic; no single, simple procedure exists for a reliable diagnosis. Prostate specific antigen (PSA), while non-invasive and easily measurable in serum, is not specific owing to false-positives from benign prostatic hyperplasia (BPH), inflammatory conditions and prostatic trauma. Additional diagnostic information must therefore be obtained by transrectal ultrasonography (TRUS) and digital rectal examination (DRE) to assess prostate size and morphology. Final c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…Some other features could also be considered as potential biomarkers because of significant statistical results although they were only present in a single LC-HRMS condition. The discriminative ability of sarcosine for prostate cancer was also evaluated (Table S1 in File S3); in keeping with several earlier reports, we found no significant difference in the sarcosine level between cancer and control groups [6], [8][10], [12], [15].…”
Section: Resultssupporting
confidence: 89%
“…Some other features could also be considered as potential biomarkers because of significant statistical results although they were only present in a single LC-HRMS condition. The discriminative ability of sarcosine for prostate cancer was also evaluated (Table S1 in File S3); in keeping with several earlier reports, we found no significant difference in the sarcosine level between cancer and control groups [6], [8][10], [12], [15].…”
Section: Resultssupporting
confidence: 89%
“…It was therefore concluded that sarcosine is not a suitable marker for prostate cancer. By comparing PSA with T-stages in the same group of patients it was found that PSA in the T1–T2 group of patients was significantly lower than in the T3–T4 group of patients confirming the well know merits and limitations of this marker [61]. Reverse phase high performance liquid chromatography (HPLC) is the most utilized technique for separation of amino acids [62,63] or peptides [64].…”
Section: Analytical Techniques For Detection Of Sarcosinementioning
confidence: 93%
“…In another published study gas chromatography (GC) and mass spectrometry (MS) were used. The results showed that the sarcosine/alanine ratios in patients with early and advanced prostate cancer were fairly constant showing no statistically significant differences between T-stages [61]. It was therefore concluded that sarcosine is not a suitable marker for prostate cancer.…”
Section: Analytical Techniques For Detection Of Sarcosinementioning
confidence: 99%
“…Finally, sarcosine has also been linked, albeit variably, to PCa for diagnosis 24 , malignancy assessment [23][24][25] , and staging 23,24,26,27 . While the evidence that sarcosine is a useful marker for PCa is debated 49,50 , we elected to add it to the present study. A more detailed review of metabolomics for PCa and our panel selection is provided in the Supplementary Information.…”
Section: Metabolite Panel For Pcamentioning
confidence: 99%